Analisis Konsep Model Kepribadian Mahasiswa Penerima KIP-Kuliah Di UIN Raden Mas Said Surakarta Menuju Era Society 5.0 - Anggi Prasetyo; Rizqita Sari Istiqomah; Muhammad Rifai; Muhammad Abdul; Dede Muhamad Azis Dede (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
KIP-Kuliah scholarships are considered sufficient to support educational issues for students who have financial limitations to pursue higher education. Apart from helping to finance education, the use of this scholarship also supports the development of soft skills for students, in which the soft skills in question are soft skill development activities designed by student affairs, specifically for KIP-College Students. Talking about the appropriate attitude for scholarship recipients referring to the challenges of the 5.0 era of society, KIP-College students should be able to make more use of the scholarships they get, both as supports in the academic and non-academic realms. The purpose of this study was to determine the personality model of KIP-College Recipient Students at UIN Raden Mas Said Surakarta which can be implemented in the academic (campus) and non-academic (social community) spheres. The research method used is descriptive qualitative with a case study approach. The data used uses primary data and secondary data, where secondary data is used to obtain additional data in research. Primary data was obtained by means of interviews, while for secondary data obtained through journal articles. The results of the study show that the personality models of KIP-College students are in accordance with the challenges of the 5.0 era of society as follows: 1) Confident, 2) Ethical, 3) Self-control, 4) Proficient in Socializing, 5) Capable of Making Decisions, 6) Adaptation. Keywords: KIP-Kuliah; Personality; Society 5.0. Era; Undergraduate Student